Механізм визначення стану економічної безпеки будівельного підприємства - Молодід, О. О. (Ways to Improve Construction Efficiency, 2013)
The mechanism of economic security, efficiency is ensured by a combination of two principles - balance and harmonization. The model definition of economic security construction company